Implementation eBudgeting Against Performance PT Primer Eka Property Through Internal Control - Yozia Josephine; Riki Riki (Tech-E, 2017)
Cost management budget applications are needed by the Company in the business process. The design of the budget system to be built aims to create a budget that will be used for a certain period and without any changes in the current period so that the system can produce an accurate report and improve the effectiveness and efficiency in determining the funds required division. Data collection method used is by doing observation, interview and literature study. The design result of this writing is a budget management system in the form of web cost so that the control in the financing required by each division and can avoid the occurrence of excess or lack of budget. Based on the results of the design and implementation of the budget draft can solve the problem in the process of financing at PT Primer Eka Property.